Pain severity ratings in the 11th revision of the International Classification of Diseases: a versatile tool for rapid assessment : research paper - Hay, Ginea; Korwisi, Beatrice; Rief, Winfried; Smith, Blair H.; Treede, Rolf-Detlef; Barke, Antonia (Pain, 2022)
An improved classification of chronic pain is included in the 11th revision of the International Classification of Diseases and Related Health Problems. For all diagnoses of chronic pain, an optional dimensional code for the chronic pain severity will supplement the categorical diagnoses. Pain severity combines pain intensity, pain-related interference, and pain-related distress. Each component is rated by the patient on a numerical rating scale (NRS) from 0 to 10 and subsequently translated into severity stages (“mild,” “moderate,” and “severe”). This study aimed to evaluate this severity code by comparing the ratings with established psychometric measures of pain-related interference and distress. An online survey was posted to self-help groups for chronic pain, and 595 participants (88.7% women, 59.5 6 13.5 years) rated each of the severity parameters (pain intensity, pain-related interference, and pain-related distress) on an NRS from 0 to 10 and completed the Pain Disability Index and the Pain Coping Questionnaire (FESV, 3 subscales). The participants reported a mean pain intensity of 6.4 6 1.9, mean pain-related interference of 6.7 6 2.1, and mean pain-related distress of 5.7 6 2.5. The respective NRS ratings showed substantial correlations with the Pain Disability Index score (r 5 0.65) and the FESV subscales (r 5 0.65, r 5 0.56, r 5 0.37). The extension code for pain severity is a valid and efficient way of recording additional dimensional pain parameters, which can be used to monitor the course of chronic pain and its treatment. The specifier’s efficiency makes it possible to use the code when a questionnaire would not be feasible due to time constraints, such as in primary care.
Gesehen am 12.06.2023